Uribe and Santos, two government programs on national security and defense against the demands of colombian people (2014)
The former president Álvaro Uribe Velez refuses the managment of the secretary of Defense and National Security directed by Juan Manuel Santos government. This has generated political instability and obstructing the interests of the nation that has been ... for more than five decades by illegal groups. These leaders, Both, Álvaro Uribe and Juan Manuel Santos, have an excellent curriculum. Their political leadership includes a huge numbers of followers. Also, both have managed punctual articles of the actual Constitution as a base for their politics, but how have they developed them? In the same way the articles that have been lnerable in the inner conflict and between these two former allies.